Strengthening Al-Islam and Muhammadiyah for Teachers in Madrasah Aliyah Muhammadiyah 13 Sei Rampah - Daulay, Mahmud Yunus; Al-Azhari, Faisal Amri (Universitas Pahlawan Tuanku Tambusai, 2026)
In today's era of diverse and multicultural society, creating an inclusive environment in educational institutions is very important. This article explores the importance of applying the values of Al-Islam and Kemuhammadiyah as the key to realizing inclusive Islamic schools. The purpose of this service is so that Muhammadiyah teachers can understand the history of Muhammadiyah well. Basically, teachers are the best role models for students to provide useful knowledge, so that with that knowledge students can have a good personality and carry out activities in daily life in accordance with the advice given by the teacher. The method in this service uses a lecture, discussion, and reflective practice approach. The results of this service show that Muhammadiyah teachers have been active in fighting for Muhammadiyah da'wah and motivating Muhammadiyah cadres to continue to be active in Muhammadiyah activities. The conclusion in this service activity is so that teachers can carry out the vision and mission of Muhammad, especially in building education in Serdang Bedagai Regency.